RE-MERK USAHA SAPI PERAH BERBASIS KEARIFAN LOKAL DI KABUPATEN JEMBER - Hary Sulaksono (UPT Penerbitan Universitas Jember)
The purpose of writing this article is to examine the potential of indigenous businesses cattle (beef and dairy cattle) which is the basis of competitive advantage Jember regency, livestock sub-sector. This paper is an approximation (approach) to know and understand the phenomenon triggers rebranding effort dairy cattle and the impact of brand equity strategy dairy cattle business. The approach in the formulation of ideas, among others, include: 1) in the province of East Java, Jember regency is a beef cattle production center with a population number 2 (two) after Sumenep regency; 2) East Java Province is the largest producer of fresh milk in Indonesia; 3) Jember district is a center for dairy development in the eastern part of East Java, with the population increasing; 4) rebranding cattle business that rely on beef cattle but can be combined with dairy cows. The result of thinking that can be learned are: 1) the accuracy of determining the rebranding strategy dairy cows; 2) capability of human resources; competitive advantage rests on innovative differentiation; 3) the role of government and stakeholders are synergistic.